2021
DOI: 10.1177/01945998211060817
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Adult Subglottic Stenosis With Spirometry and Dyspnea Index: A Novel Approach

Abstract: Objective The aim was to examine the correlations among the anatomic Cotton-Myer classification, pulmonary function tests (PFTs), and patient-perceived dyspnea or dysphonia in patients with subglottic stenosis and identify measurements accurately reflecting treatment effects. Study Design Prospective cohort study. Setting Tertiary referral center. Method Fifty-two adults receiving endoscopic treatment for isolated subglottic stenosis were consecutively included. Correlations were calculated among the preoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…These groundbreaking works are further consolidated by our data, extending the evidence that EDI could differentiate particularly SGS from both asthma and COPD, the two diagnoses implicated in the diagnostic delay of this condition. Together with other studies discussing EDI’s role in monitoring the treatment effects of patients with subglottic stenosis, our study clearly spotlights the main benefit of extracting the EDI routinely from conventional spirometry [ 14 , 19 , 20 , 32 ].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These groundbreaking works are further consolidated by our data, extending the evidence that EDI could differentiate particularly SGS from both asthma and COPD, the two diagnoses implicated in the diagnostic delay of this condition. Together with other studies discussing EDI’s role in monitoring the treatment effects of patients with subglottic stenosis, our study clearly spotlights the main benefit of extracting the EDI routinely from conventional spirometry [ 14 , 19 , 20 , 32 ].…”
Section: Discussionsupporting
confidence: 65%
“…Although DI showed a good AUC, it is practically nonfunctional in distinguishing SGS from nonstenosis considering that the cutoff value of 25 points is quite high, combined with a considerably lower sensitivity and specificity when compared to EDI. In our view, DI could further be used as a complementary measurement for assessing dyspnea in patients already diagnosed with upper airway obstruction, potentially affecting the decision-making and priority of a surgical intervention, as shown by other studies [ 17 19 ].…”
Section: Discussionmentioning
confidence: 71%
“…Song et al [ 34 ] showed the poor interrater reliability of a visual estimation in Cotton–Myer grading among physicians and further discussed the difficulty in identifying cricoid cartilage when assessing stenosis length endoscopically. Moreover, neither of the two systems correlates with functional airway assessment with spirometry, as shown by several studies [ 35 37 ]. Since there is evidence that several measurements of pulmonary function could be used in the diagnosis and postoperative monitoring of patients with SGS [ 34 , 35 ], the lack of a preoperative functional evaluation with spirometry in our study population is considered another shortcoming of our study.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, neither of the two systems correlates with functional airway assessment with spirometry, as shown by several studies [ 35 37 ]. Since there is evidence that several measurements of pulmonary function could be used in the diagnosis and postoperative monitoring of patients with SGS [ 34 , 35 ], the lack of a preoperative functional evaluation with spirometry in our study population is considered another shortcoming of our study. Moreover, it would be interesting to quantify patient-experienced dyspnea using questionnaires specifically developed for upper airway obstruction [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 95%
“…No preoperative respiratory function tests were performed. SGS can be diagnosed based on extra-thoracic airway obstruction predicted by an expiratory disproportion index (the ratio of FEV1 to peak expiratory flow rate) > 0.5 [6]. In this case, a respiratory function test could have predicted the possibility of upper airway stenosis, and CT images could have helped in the early diagnosis of SGS, considering the patient history.…”
Section: Discussionmentioning
confidence: 99%